Physical Learning Ecosystem and Built Environment of Tahfiz Institutions in Malaysia: A Systematic Review - Awang, Arita Hanim; Ab Jalil, Nurlelawati; Salleh, Nurul Hamiruddin; Ab. Jalil, Habibah; Salim, Siti Suria (2019)
Tahfiz education is common in Malaysia referring to the Islamic education system of producing ‘Hufaz’ or graduates who can memorize and recite the Quran. This study covers all types of Quran memorizing institutions in Malaysia namely, Pondok, Madrasah, Maahad, Centre and Institute. The aim of this systematic review is to identify the type of physical learning ecosystem (PLE) and the aspect of the built environment (BE) of the Tahfiz Institution (TI) in Malaysia. The research starts by defining the PLE and BE to establish the related variables to extracts from the literature. The keywords are also identified and established. The study covers a systematic literature search available from Google Scholars, Scopus, Web of Science, Crossref and Grey Literature. The scope of the literature chosen is specifically related to the Malaysian context. The quantitative synthesis of related research studies was used. The literature on PLE and BE of TI in Malaysia are still lacking as the areas are rarely examined directly, therefore content analysis of the related articles are used to establish the research findings. This research provides a summary of available studies on the PLE of Malaysian TI and BE features. The findings confirm that the lack of literature and studies on the BE aspects of TI in Malaysia highlighted the importance of the studies to upgrade the current infrastructure of TI. In addition to that, the research emphasizes the needs to acquire primary data of the existing conditions of and of the TI in Malaysia.